Natural Pigments from Gardenia jasminoides J. Ellis and Peristrophe bivalvis (L.) Merr for Food Coloring - Pham Thi Luong Hang; Le Thuy Ngan; Tran Thi Lan Phuong; Nguyen Lai Thanh; Yuki Ishikawa-Ishiwata; Dang Minh Hieu; Nguyen Dinh Thang (Journal of Food Quality)
Food coloring not only provides an attractive appearance but also aids in the quality of the food. Currently, colorants derived from natural sources, especially plants, are widely used for food coloring, with many benefits for health and the environment. This study used yellow and purple pigments extracted from Gardenia fruits and Peristrophe leaves for chemical component analysis and antioxidant and toxicity tests. Results from LC/MS analysis demonstrated that the major compounds contributing to the yellow color of the Gardenia extract and purple color of the Peristrophe extract were Crocin-1 (C44H64O24) and Perisbivalvine B (C13H10N2O4), respectively. Moreover, the physiochemical tests showed that yellow and purple pigments were stable in a wide temperature range from 40 to 100°C. The yellow pigment was stable in a pH range of 1.0–12.0, while the purple pigment was not stable in acid media. These extracts also possessed moderate antioxidant activities with IC50 values of 0.33 g/L and 0.31 g/L for Gardenia and Peristrophe extract, respectively. In addition, toxicity tests on zebrafish embryos indicated that these extracts had low toxic activities with high LD50 values of 1.31 g/L for Gardenia extract and 0.74 g/L for Peristrophe extract. These tested extracts had also no acute toxicity on mice. Conclusively, this study provided important information about the major chemical components, which create yellow and purple colors for the Gardenia and Peristrophe extracts, and strongly suggested that the pigments extracted from Gardenia and Peristrophe can be safely used as food colorants.